Plasmonic Titanium Nitride Facilitates Indium Oxide CO2 Photocatalysis. Issue 49 (17th November 2020) - Nguyen, Nhat Truong; Yan, Tingjiang; Wang, Lu; Loh, Joel Yi Yang; Duchesne, Paul N.; Mao, Chengliang; Li, Pei‐Cheng; Jelle, Abdinoor A.; Xia, Meikun; Ghoussoub, Mireille; Kherani, Nazir P.; Lu, Zheng‐Hong; et al.
Abstract: Nanoscale titanium nitride TiN is a metallic material that can effectively harvest sunlight over a broad spectral range and produce high local temperatures via the photothermal effect. Nanoscale indium oxide‐hydroxide, In2 O3− x (OH) y, is a semiconducting material capable of photocatalyzing the hydrogenation of gaseous CO2 ; however, its wide electronic bandgap limits its absorption of photons to the ultraviolet region of the solar spectrum. Herein, the benefits of both nanomaterials in a ternary heterostructure: TiN@TiO2 @In2 O3− x (OH) y are combined. This heterostructured material synergistically couples the metallic TiN and semiconducting In2 O3− x (OH)y phases via an interfacial semiconducting TiO2 layer, allowing it to drive the light‐assisted reverse water gas shift reaction at a conversion rate greatly surpassing that of its individual components or any binary combinations thereof. Abstract : TiN@TiO2 @In2 O3− x (OH) y combines the benefits of surface plasmon and photothermal effect of TiN, interfacial charge transfer TiO2 layer, and photocatalyzing In2 O3− x (OH) y . The choice and precise arrangement of three components allow for a controlled flow of photogenerated electrons and phonons that drives CO2 hydrogenation reaction at an elevated rate which excels its individual and binary components.